Perpindahan panas dan massa pada pengembunan campuran etanol-benzen-udara dalam kondensor tegak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Condensation of vapor-gas mixtures is a simultaneous heat and mass transfer processes. The existence of gases in condensation does not only affect the heat transfer rate, but also the mass transfer rate. Theoretical studies on condensation of vapor and gas mixtures have been done extensively, but have not given satisfactory results yet. The objective of the research is to determine semi-empirical equations, which are simple and accurate enough, to estimate the heat and mass transfer coefficients for the ethanol-benzene-air mixture. The experiment was conducted in a vertical double pipe condenser of 1.7 m length. The inner and outer pipe sizes were, respectively, 1" and 2". The mixture of vapors and gas was flowing in annulus from the top of the condenser and cooling water was counter-currently flowing inside the tube. The gas mole fractions used were between 1% and 10 % and the Reynolds number were between 2000 and 20600. The relationship of heat and transfer coefficients evaluated based on the experimental data using simple mathematical models can be expressed in the following equations.